1996
DOI: 10.1007/bf01886751
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the antibody-binding regions on botulinum neurotoxin H-chain domain 855–1296 with antitoxin antibodies from three host species

Abstract: Botulism due to food poisoning is caused mainly by protein toxins, botulinum neurotoxins (BoNTs), produced by Clostridium botluinum in seven known immunological serotypes. These are the most potent toxins and poisons known. BoNT effects blockade of neuromuscular transmission by preventing neurotransmitter release. Human botulism is most frequently caused by types A, B, and E. Recent studies have shown that immunization with a 43-kDa C-terminal fragment (Hc, residues 860-1296) of BoNT/A affords excellent protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 60 publications
2
65
0
1
Order By: Relevance
“…This is consistent with the observation that BoNTs can be cleared by combinations of monoclonal antibodies that do not neutralize toxin activity (59). Furthermore, work by Atassi and his coworkers identified the peptide composing the GPB as a minor yet reproducible immunological epitope, though dominant epitopes varied by species (58).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with the observation that BoNTs can be cleared by combinations of monoclonal antibodies that do not neutralize toxin activity (59). Furthermore, work by Atassi and his coworkers identified the peptide composing the GPB as a minor yet reproducible immunological epitope, though dominant epitopes varied by species (58).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, neutralizing antibodies that target the light chain of BoNT/A through another mechanism, potentially by preventing translocation of the LC but not endocytosis of the holotoxin, have been found (54)(55)(56). Numerous epitopes on both the N-and C-terminal regions of HCR/A have been described, and neutralizing activity is absent from antibodies that target the N terminus, distal to the GBP (17,30,57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Atassi and Dolimbek used polyclonal antisera to compare the responses of humans and other animal species to peptides from Botulinum neurotoxin (19,20). These authors observed that antisera from different animals often recognized similar regions on the antigen, but found there were boundary frame shifts and differences in immunodominance of specific regions among the antisera.…”
Section: Discussionmentioning
confidence: 99%
“…The efforts in the laboratory of Atassi and coworkers have focused on the development of a synthetic vaccine against BoNT intoxication [42,43]. The investigators synthesized a series of overlapping 19-mer peptides that spanned the entire H C region of BoNT serotype A (BoNT/ A).…”
Section: Other Strategies For Developing a Bont Vaccinementioning
confidence: 99%